What to expect when you're expecting - Murkoff, Heidi Eisenberg; Eisenberg, Arlene; Hathaway, Sandee Eisenberg (New York : Workman Pub., 2002)
We're expecting again! Announcing the completely revised and updated third edition of America's best-selling pregnancy book, What to Expect When You're Expecting. Two years in the making, it's a cover-to-cover, chapter-by- chapter, line-by-line revision and update. Everything that the original did-which, at just shy of 10 million copies in print, it did extraordinarily well-the third edition does, and better. Incorporating the most recent developments in medicine, and responding to the many queries and letters received from readers, the book contains both the most accurate information available, and the most reader-friendly. The third edition includes more information on working while pregnant. It offers more in- depth coverage of complementary and alternative birthing. Greater attention is paid to pre-conception, alternative families, second pregnancies, HMOs, the role of the father, and lifestyle. There's a completely new look at the best- odds diet, which is better suited to the needs of busier women with less time. An updated cover and all-new black- and-white illustrations give the classic a fresher look
Are you pregnant? Choosing (and working with) your practitioner -- Now that you're pregnant. About prenatal diagnosis ; Screening tests ; Diagnostic tests -- Throughout your pregnancy. Putting risk in perspective -- The pregnancy diet. The food selection groups ; The recipes -- The first month (approx. 1 to 4 weeks). Getting regular medical care -- The second month (approx. 5 to 8 weeks). Playing it safe -- The third month (approx. 9 to 13 weeks). Weight gain during pregnancy -- The fourth month (approx. 14 to 17 weeks). Exercise during pregnancy -- The fifth month (approx. 18 to 22 weeks). Making love during pregnancy -- The sixth month (approx. 23 to 27 weeks). Childbirth education -- The seventh month (approx. 28 to 31). About childbirth medication -- The eighth month (approx. 32 to 35 weeks). About breastfeeding -- The ninth month (approx. 36 to 40 weeks). About prelabor, false labor, real labor -- Labor and delivery. The stages and phases of childbirth ; The first stage of childbirth : labor ; The second stage of childbirth : pushing and deliver ; The third stage of childbirth : delivery of the placenta or afterbirth ; Breech delivery ; Cesarean section : surgical delivery -- Postpartum : the first week. Getting started breastfeeding -- Postpartum : the first six weeks. Getting back into shape -- Fathers are expectant, too -- If you get sick. Staying well -- Coping with a chronic condition. Living with the high-risk or problem pregnancy -- When there's a problem. Pregnancy complications ; Uncommon pregnancy complications ; Childbirth and postpartum complications ; Coping with pregnancy loss -- Preparing for the next baby -- Appendix. Common tests during pregnancy ; Non-drug treatments during pregnancy ; Pregnancy calorie and fat requirements ; Sources and resources
Includes index
cover illustrations by Judith Cheng; interior illustrations by Judy Francis
Keywords: Pregnancy; Childbirth; Postnatal care; Pregnancy -- Popular Works; Labor, Obstetric -- Popular Works; Postnatal Care -- Popular Works